2007
DOI: 10.1007/s10641-007-9214-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing temperature on sex ratio in juvenile Atlantic halibut, Hippoglossus hippoglossus

Abstract: Several flatfish species exhibit temperature-dependent sex determination. This research investigated the effects of rearing temperature on sex ratio in Atlantic halibut, Hippoglossus hippoglossus, a species in which females grow larger and faster than males under culture conditions. Previous research has shown that ovarian differentiation occurs in Atlantic halibut in the size interval of 38-50 mm, and precedes the differentiation of testes. In the current study, triplicate groups of juvenile Atlantic halibut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This information was obtained mainly from sex ratios in progenies of meiogynogenetics and triploids, and both XX/XY and ZZ/ZW mechanisms have been reported (Purdom 1972;Tabata 1991;Howell et al 1995;Tvedt et al 2006;Chen et al 2009). Environmental factors, such as temperature, do (Tabata 1995;Goto et al 1999;Luckenbach et al 2005) or do not affect (Hughes et al 2008) gonad differentiation in flatfish, but this appears not to be a primary factor in sex determination in this group (OspinaAlvarez and Piferrer 2008). Segregation patterns of the closest markers to the SD region in turbot support a ZZ/ZW mechanism in the five families analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This information was obtained mainly from sex ratios in progenies of meiogynogenetics and triploids, and both XX/XY and ZZ/ZW mechanisms have been reported (Purdom 1972;Tabata 1991;Howell et al 1995;Tvedt et al 2006;Chen et al 2009). Environmental factors, such as temperature, do (Tabata 1995;Goto et al 1999;Luckenbach et al 2005) or do not affect (Hughes et al 2008) gonad differentiation in flatfish, but this appears not to be a primary factor in sex determination in this group (OspinaAlvarez and Piferrer 2008). Segregation patterns of the closest markers to the SD region in turbot support a ZZ/ZW mechanism in the five families analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Meiotic gynogenetic H. hippoglossus were all-female, suggesting an XX/XY sex-determining system [16]. Temperature has not been shown to have an effect on H. hippoglossus sex ratio [17]. Gonadal sex differentiation can be manipulated through in-feed synthetic steroid treatments ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The sex of the larvae determined was assessed in 20 specimens per treatment every week, from 110 DPH to 173 DPH. This time chosen was from a previous study of another flatfish, Hippoglossus hippoglossus , which showed that sexual differentiation occurred on 140 DPH (Hughes et al, 2008).…”
Section: Methodsmentioning
confidence: 99%